2019
DOI: 10.3233/jnd-180341
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of Edasalonexent (CAT-1004), an Oral NF-κB Inhibitor, in Pediatric Patients with Duchenne Muscular Dystrophy

Abstract: Background: Edasalonexent is an orally administered small molecule designed to inhibit NF- κ B, which is activated from infancy in Duchenne muscular dystrophy and is central to causing muscle damage and preventing muscle regeneration. Objective: Evaluate the safety, tolerability, pharmacokinetics and exploratory pharmacodynamics of three doses of edasalonexent in ambulatory males ≥4 to <8 years of age with genetically confirmed Duchenne muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…As the identification of effective small molecule therapeutics to combat inflammation, fibrosis, and muscle wasting in DMD and BMD will continue to remain an unmet medical need, our findings highlight the importance of evaluating candidate therapeutic efficacy in combination with standard-of-care therapies. Additionally, these data further support the rationale to explore alternative standard-of-care regimens for dystrophinopathy patients other than chronic glucocorticoids, such as intermittent glucocorticoid dosing (12) and/or nonsteroidal NF-κB inhibitors (68,69), both of which demonstrate efficacy and safety without promoting skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 64%
“…As the identification of effective small molecule therapeutics to combat inflammation, fibrosis, and muscle wasting in DMD and BMD will continue to remain an unmet medical need, our findings highlight the importance of evaluating candidate therapeutic efficacy in combination with standard-of-care therapies. Additionally, these data further support the rationale to explore alternative standard-of-care regimens for dystrophinopathy patients other than chronic glucocorticoids, such as intermittent glucocorticoid dosing (12) and/or nonsteroidal NF-κB inhibitors (68,69), both of which demonstrate efficacy and safety without promoting skeletal muscle atrophy.…”
Section: Discussionmentioning
confidence: 64%
“…five patients for the AMPK activator, metformin) or the short‐term duration of the treatment (i.e. 1 week for the NF‐κB inhibitor, CAT‐1004). Trials with the utrophin up‐regulator (Ezutromid®) turned out to be disappointing and have been recently stopped (http://www.musculardystrophynews.com).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic activation of nuclear factor (NF) kB drives muscle degeneration and suppresses muscle regeneration in DMD. 27 Edasalonexent inhibits NF-kB-dependent inflammatory responses and downstream proinflammatory genes, and therefore it may play a role in replacing steroids for these patients. A phase 1/2 study showed it was well tolerated and inhibited the NF-kB pathways, 27 and a phase 3 study is currently underway (NCT03703882).…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…27 Edasalonexent inhibits NF-kB-dependent inflammatory responses and downstream proinflammatory genes, and therefore it may play a role in replacing steroids for these patients. A phase 1/2 study showed it was well tolerated and inhibited the NF-kB pathways, 27 and a phase 3 study is currently underway (NCT03703882). In August 2018, the development of domagrozumab, a monoclonal antibody inhibitor of myostatin, was terminated after the drug did not meet the primary efficacy end point in a phase 2 clinical trial.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%